2016
DOI: 10.1016/j.nano.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Magneto acoustic tomography with short pulsed magnetic field for in-vivo imaging of magnetic iron oxide nanoparticles

Abstract: Nanoparticles are widely used as contrast and therapeutic agents. As such, imaging modalities that can accurately estimate their distribution in-vivo are actively sought. We present here our method Magneto Acoustic Tomography (MAT), which uses magnetomotive force due to a short pulsed magnetic field to induce ultrasound in the magnetic nanoparticle labeled tissue and estimates an image of the distribution of the nanoparticles in-vivo with ultrasound imaging resolution. In this study, we image the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 56 publications
0
25
0
2
Order By: Relevance
“…In 2016, Mariappan and others successfully detected and reconstructed the MNPs distribution in mice with MNPs in vivo using MAT-MI. The experiment proved that the MAT-MI based on MNPs had good resolution and imaging depth [12]. In 2018, Yan and other researchers studied the influence of MNPs on MAT-MI from a theoretical point of view and determined that MNPs can make the reconstruction of sound sources more convenient because MNPs can produce more sound pressure signals and more uniform sound pressure distribution than traditional MAT-MI.…”
Section: Introductionmentioning
confidence: 94%
“…In 2016, Mariappan and others successfully detected and reconstructed the MNPs distribution in mice with MNPs in vivo using MAT-MI. The experiment proved that the MAT-MI based on MNPs had good resolution and imaging depth [12]. In 2018, Yan and other researchers studied the influence of MNPs on MAT-MI from a theoretical point of view and determined that MNPs can make the reconstruction of sound sources more convenient because MNPs can produce more sound pressure signals and more uniform sound pressure distribution than traditional MAT-MI.…”
Section: Introductionmentioning
confidence: 94%
“…The most possible clinical application of MAT-MI is believed to be tumor detection especially in cancer screening and detection. A recent work on magneto acoustic tomography with the aid of magnetic nanoparticles suggested such possibility; employing the magnetomotive force, magneto acoustic tomography in a MAT-MI compatible setup was demonstrated as a high-spatial-resolution approach to reconstruct the in vivo distributions of nanoparticles, and to further highlight tumor by a high contrast (Mariappan et al, 2016). This study sheds light on the possibility of improving magnetoacoustic imaging by harnessing the versatility of nanoparticles.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Magnetic nanoparticles (NPs) with good superparamagnetic behavior have attracted much attention, due to their inherent material properties and huge potential in cancer diagnosis [9][10][11] and treatment. 12 Our previous studies have demonstrated that thermosensitive hydrogel systems including Fe 3 O 4 magnetic NPs prolonged the retention of chemotherapy drugs in bladders with external magnets.…”
Section: Introductionmentioning
confidence: 99%